2022
DOI: 10.1021/acs.biomac.2c00482
|View full text |Cite
|
Sign up to set email alerts
|

Phenylboronic Acid-Functionalized Copolypeptides: Facile Synthesis and Responsive Dual Anticancer Drug Release

Abstract: The incorporation of a phenylboronic acid group has appeared as an attractive strategy to build smart drug delivery systems. Here, we report novel synthesis of phenylboronic acid-functionalized copolypeptides based on an L-boronophenylalanine Ncarboxyanhydride (BPA-NCA) monomer and their application for robust co-encapsulation and responsive release of dual anticancer drugs. By employing different poly(ethylene glycol) (PEG) initiators and copolymerizing with varying NCA monomers, linear and star PEG-poly(L-bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…NP was constructed through the self-assembly of PEG-b-P(BPAco-Tyr) copolymer that was synthesized by simultaneous copolymerization of BPA-NCA and Tyr-NCA monomers in the presence of PEG-NH 2 (M n = 5.0 kg mol −1 ) as previous report (Scheme S1, Supporting Information). [19] 1 H NMR spectrum of 1), corroborating that the NCA copolymerization proceeded in a controlled manner and copolypeptides with tailored chain length and functionalities could be readily obtained. MALDI-TOF and gel permeation chromatography (GPC) measurements revealed that PEGb-P(BPA-co-Tyr) had similar molecular weights to those measured by 1 H NMR and narrow polydispersities with an M w /M n of around 1.10 (Figure 1E, Table 1).…”
Section: Construction and Characterization Of Dual Inhibitor-loaded N...mentioning
confidence: 56%
See 2 more Smart Citations
“…NP was constructed through the self-assembly of PEG-b-P(BPAco-Tyr) copolymer that was synthesized by simultaneous copolymerization of BPA-NCA and Tyr-NCA monomers in the presence of PEG-NH 2 (M n = 5.0 kg mol −1 ) as previous report (Scheme S1, Supporting Information). [19] 1 H NMR spectrum of 1), corroborating that the NCA copolymerization proceeded in a controlled manner and copolypeptides with tailored chain length and functionalities could be readily obtained. MALDI-TOF and gel permeation chromatography (GPC) measurements revealed that PEGb-P(BPA-co-Tyr) had similar molecular weights to those measured by 1 H NMR and narrow polydispersities with an M w /M n of around 1.10 (Figure 1E, Table 1).…”
Section: Construction and Characterization Of Dual Inhibitor-loaded N...mentioning
confidence: 56%
“…Boronic ester bonds not only promote strong interactions of drugs with nanovehicles under physiological conditions, but also provide acid/H 2 O 2 ‐triggered responsivity. [ 19,21 ] Indeed, NPAT revealed obvious dissociation and swelling after incubating in phosphate buffered salt (PBS) (pH 5.5) or PBS with 100 × 10 −6 m H 2 O 2 for 6 h (Figure 1J). Besides, enzymes like proteinase K (PK) could induce the nanoparticle swelling and aggregation as characterized by the presence of new bands at around 800 and 8000 nm owing to the enzymatic degradation of polypeptide segments.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…31 In contrast to the other type of linkage like ester, it was revealed that curcumin-loaded drug carriers via boronate ester show a burst release within the first two days and later with a sustained release. 32–34 The drug release pattern showed 40% burst release during 1st day, followed by a 75% overall release at pH 6, and 25% burst release during 1st day, followed by a 57% overall release at pH 7.4. As seen in the release profile, the release rate was faster in acidic pH than in neutral, because the borate ester could be cleaved under acidic conditions, thereby facilitating faster curcumin elution.…”
Section: Resultsmentioning
confidence: 98%
“…Taking advantage of the “like dissolves like” mechanism, PMs-CFZ presented a decent drug loading level with a drug loading content (DLC) up to 11.2 wt % (Figure A). The introduction of extra physical interactions including π–π stacking, hydrogen bonding, and coordination has been proven to benefit drug loading and stability. In contrast, less than 4.5 wt % of DLC was accomplished for CFZ in liposome and polycarbonate-based nanosystems. ,, DLS measurement demonstrated that PMs-CFZ had an average diameter of lower than 85 nm and a narrow distribution (PDI < 0.16).…”
Section: Results and Discussionmentioning
confidence: 99%